2002
DOI: 10.5194/angeo-20-1843-2002
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of night-time enhancement of TEC at a low latitude station on storm and quiet nights including the local time, seasonal and solar activity dependence

Abstract: Abstract. The main characteristics of night-time enhancements in TEC during magnetic storms are compared with those during quiet nights for different seasons and solar activity conditions at Palehua, a low latitude station during the period 1980-1989. We find that the mean amplitude has both a seasonal and solar activity dependence: in winter, the values are higher for weak storms as compared to those during quiet nights and increase with an increase in solar activity. In summer, the mean amplitude values duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…This leads to severe dissipation of LSTIDs, even if they were traveling during the night. Strong nighttime enhancements in TEC are usually observed at low latitudes during both disturbed and quiet times (Unnikrishnan et al, 2002;Jain et al, 2011), and dissipation of LSTIDs due to ion drag has previously been reported by Tsugawa et al (2004) and Ding et al (2012).…”
Section: Annmentioning
confidence: 56%
“…This leads to severe dissipation of LSTIDs, even if they were traveling during the night. Strong nighttime enhancements in TEC are usually observed at low latitudes during both disturbed and quiet times (Unnikrishnan et al, 2002;Jain et al, 2011), and dissipation of LSTIDs due to ion drag has previously been reported by Tsugawa et al (2004) and Ding et al (2012).…”
Section: Annmentioning
confidence: 56%
“…Nighttime enhancements in TEC had been reported in previous studies (e.g. Mukherjee et al, 2010;Adewale et al, 2012;D'ujanga et al, 2012;Oron et al, 2013;Aggarwal, 2011;Unnikrishnan et al, 2002). This enhancement in TEC could be attributed to enhancement of eastward electric field which causes the equatorial ionization anomaly.…”
Section: Diurnal Tec Variationsmentioning
confidence: 59%
“…The observed features of the nighttime enhancements in the total ionospheric electron content, TEC, at low geomagnetic latitudes, were reported by various workers (e.g. Young et al, 1970;Nelson and Cogger, 1971;Lanzerotti et al, 1975;Tyagi et al, 1982;Balan et al, 1994;Su et al, 1994;Jain et al, 1995;Unnikrishnan et al, 2002). The post-sunset enhancements in TEC and NmF2 of the low-latitude ionosphere during geomagnetically quiet conditions were studied by Anderson and Klobuchar (1983), Dasgupta et al (1985), Balan et al (1995), and Su et al (1995Su et al ( , 1997, using theoretical modeling techniques.…”
mentioning
confidence: 99%